Advances in Xenotransplantation: Evaluation of αGal-KO Porcine Livers and Lungs Using Normothermic Machine Perfusion in a Collaborative Perfusion Hub - S. Stoerzer; S. Kruszona; P. Wand; H. Linge; H. Zlatev; K. Hoeffler; K. Hoeffler; J. Singh; N. Roters; N. Roters; V. Muth; S. Tavil; et al. (Transplant International)
Recently, initial clinical experience has been gained with the xenotransplantation of pig organs such as heart and kidney into terminally ill human patients in an effort to overcoming organ shortage. Here, we investigated the use of normothermic machine perfusion (NMP) to advance xenotransplantation research and develop bridging therapies for acute organ failure such as the use of pig livers as a liver dialysis system. We simultaneously analyzed livers and lungs from genetically modified pigs, carrying a knock-out of the GGTA1 gene, which is essential for xenoreactive αGal-KO-epitopes, by applying clinically established normothermic perfusion systems, solutions and human blood. Experiments involved perfusing organs with cell-free solutions as well as human erythrocyte concentrates for up to six hours, analyzing organ quality using invasive and non-invasive methods, and the isolation and analysis of immune cells from the perfusate. The results obtained show stable flow characteristics with physiological perfusion and oxygenation levels of the organs, and a largely intact organ architecture, confirmed by histological sections before and after perfusion. Overall, this study demonstrates the feasibility of normothermic machine perfusion of xenogeneic organs by an interdisciplinary team, thus paving the way for clinical applications of porcine xenografts involving NMP.